2022
DOI: 10.1038/s41598-022-14453-x
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric method to measure in vitro nitrogenase functionality for engineering nitrogen fixation

Abstract: Biological nitrogen fixation (BNF) is the reduction of N2 into NH3 in a group of prokaryotes by an extremely O2-sensitive protein complex called nitrogenase. Transfer of the BNF pathway directly into plants, rather than by association with microorganisms, could generate crops that are less dependent on synthetic nitrogen fertilizers and increase agricultural productivity and sustainability. In the laboratory, nitrogenase activity is commonly determined by measuring ethylene produced from the nitrogenase-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…3c). This indicated that OsNifM Av expression was sufficient in all three rice lines, which was consistent with recent results obtained in S. cerevisiae 22 .…”
Section: Co-expression Of Osnifhsupporting
confidence: 93%
See 2 more Smart Citations
“…3c). This indicated that OsNifM Av expression was sufficient in all three rice lines, which was consistent with recent results obtained in S. cerevisiae 22 .…”
Section: Co-expression Of Osnifhsupporting
confidence: 93%
“…The nifH Ht gene was placed under a stronger promoter than nifM Av because the former encodes the most abundant Nif protein and it is part of the nitrogenase complex. Although there is no study proving that NifM is essential for NifH in plant mitochondria, NifM has been shown to be required for NifH solubility in heterologous expression systems including E. coli , yeast mitochondria, and plant chloroplasts 14 , 16 , 22 . Although we were unable to obtain clear western blot signals for Os NifM Av in the plant extracts, the fact that Os NifH Ht was soluble indicated that Os NifM Av was expressed at sufficient levels to facilitate NifH polypeptide maturation, as recently shown for NifH Ht in S. cerevisiae 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…nifH is a marker gene, and researchers have been able to characterize aspects of the diversity and ecology of nitrogen-fixing bacteria and archaea. The biological nitrogen fixation of plants, rather than by association with microorganisms, can generate crops that are less dependent on synthetic nitrogen fertilizers and can increase agricultural productivity and sustainability [ 50 ]. The sweet potato, the seventh largest food crop in the world [ 2 ], grows well in nitrogen-poor infertile soils, and it is believed that sweet potato endo- and epiphytic microorganisms play important roles in acting upon this growth ability in this plant [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, a new spectrophotometric method to measure nitrogenase activity has been developed. 25 Similarly, quantification of hydrogenase can be done spectrophotometrically via the reduction product of methyl viologen, which is oxidized by the hydrogenase enzyme. 26 These biological catalysts are responsible for the metabolic mechanism associated with the formation and production of biohydrogen, with biological engineering required to further optimize the interaction of the enzymes with the substrate, in this case, organic materials.…”
Section: Screening Of Seaweed Suitability Via Compositional Analysis ...mentioning
confidence: 99%